Anti-parasitic activity of pelleted sainfoin (Onobrychis viciifolia) against Ostertagia ostertagi and Cooperia oncophora in calves. Issue 1 (December 2016) - Desrues, Olivier; Peña-Espinoza, Miguel; Hansen, Tina; Enemark, Heidi; Thamsborg, Stig
Abstract Background Increasing anthelmintic-resistance in nematodes of ruminants emphasises the need for sustainable parasite control. Condensed tannin-containing legume forages such as sainfoin (Onobrychis viciifolia ) have shown promising anthelmintic properties in small ruminants but this has never been explored in cattle. Therefore, our aim was to examine the efficacy of sainfoin against cattle nematodes in vivo. Methods Fifteen Jersey male calves (2–4 month-old) were allocated into two groups and fed isoproteic and isoenergetic diets mainly composed of sainfoin pellets (Group SF;n  = 9, three pens) or concentrate and grass-clover hay (Group CO;n  = 6, two pens). After 16 days of adaptation, all animals were experimentally infected with 10, 000 and 66, 000 third-stage larvae ofOstertagia ostertagi andCooperia oncophora, respectively. Egg excretion, blood parameters and bodyweights were recorded throughout the study. Worms were harvested by sieving for quantification and scanning electron microscopy (SEM) 42 days post-infection (dpi) when the calves were necropsied. Results The number ofO. ostertagi adults in the abomasum was reduced by 50 % in Group SF compared with Group CO (P  < 0.05). This was further reflected in higher albumin (P  < 0.1) and lower pepsinogen levels (P  < 0.05) in Group SF at 21 dpi, and structural damage of the worm cuticle could be visualised by SEM. Yet, the nematode egg excretion in Group SF was not significantly different from that of the controls (P  > 0.05). Likewise, no statistical difference in total worm burdens ofC. oncophora was found between the groups. Weight gains were lower for Group SF (P  < 0.05), which may reflect lower digestibility and phosphorus levels in the SF diet, despite similar feed intake at pen-level. Conclusions Overall, the effect of sainfoin on abomasal nematodes corroborates results from studies with small ruminants and encourages further investigations of the use of this crop for control of cattle nematodes.